Engaging the six cultures of the academy revised and expanded edition of The four cultures of the academy - Bergquist, William H.; Pawlak, Kenneth, 1953- (The Jossey-Bass higher and adult education series, 2008)
In The Four Cultures of the Academy, William H. Bergquist identified four different, yet interrelated, cultures found in North American higher education: collegial, managerial, developmental, and advocacy. In this new and expanded edition of that classic work, Bergquist and coauthor Kenneth Pawlak propose that there are additional external influences in our global culture that are pressing upon the academic institution, forcing it to alter the way it goes about its business.